Relaciones entre la regulación de las emociones y los síntomas de depresión y ansiedad: un análisis de redes - Vizioli , Nicolás (2025)
Symptoms seem to be constitutive parts of a complex clinical problem, rather than the expressions of a disease, as traditionally considered. Network analysis has proved to be useful to identify correlations amongst them. This study addresses associations regarding regulation strategies and depressive and anxious symptoms, as well as emotion regulation strategies’ risk and protective ability, in a sample of 1103 adults from Buenos Aires City and Greater Buenos Aires aged between 18 and 65 (M= 31.96; SD= 10.32). Results showed that CR and ES might be differentially associated with anxiety and depression symptoms, yet both exhibited negative bridge expected influence across the networks, suggesting a protective role. These findings have several implications for treatments.